Potensi Pencemaran Nama Baik Dalam Gerakan “Naming And Shaming” Bagi Pelaku Tindak Pidana Kekerasan Seksual - Sahid Yudhakusuma Kalpikajati; Riska Andi Fitriono (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2024)
Nowadays, with advances in information technology and the emergence of the internet, people are carrying out the